2019
DOI: 10.1016/j.poetic.2019.03.002
|View full text |Cite
|
Sign up to set email alerts
|

The effects of parents’ lifestyle on their children’s status attainment and lifestyle in the Netherlands

Abstract: Les documents de travail ne reflètent pas la position du CREST et n'engagent que leurs auteurs. Working papers do not reflect the position of CREST but only the views of the authors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 36 publications
1
8
0
2
Order By: Relevance
“…It could be elucidated that the socioeconomic status of parents influences the mathematics learning outcomes of fifthgrade students of MI Islamiyah Karangpakel. This result was in line with Sudarsana (2018) that student learning outcomes, which have poor economic levels of parents experience the obstacles, whereas student learning outcomes of capable economic levels do not experience obstacles (Nagel & Lemel, 2019).…”
Section: Discussionsupporting
confidence: 79%
“…It could be elucidated that the socioeconomic status of parents influences the mathematics learning outcomes of fifthgrade students of MI Islamiyah Karangpakel. This result was in line with Sudarsana (2018) that student learning outcomes, which have poor economic levels of parents experience the obstacles, whereas student learning outcomes of capable economic levels do not experience obstacles (Nagel & Lemel, 2019).…”
Section: Discussionsupporting
confidence: 79%
“… See Lizardo and Skiles (2012, 2015) for an explication of the foundational concepts that have been animating the study of class stratification and tastes. These concepts are most strongly associated with the work of Pierre Bourdieu and Richard Peterson.2 Note that this strict reading of Bourdieu's argument is in contrast with a great deal of Bourdieusian-inspired research that has found that family socialization into consecrated tastes in childhood produces a tendency to have tastes for consecrated culture in adulthood (e.g.,Nagel and Lemel 2019).3 Prior work that finds an association between education and omnivorousness (seePeterson [2005] for review) crucially does so at the genre level. To be clear, our argument is not that in the accumulation of capital, familial socialization is only ultimately expressed through genre-level openness and that education is only ultimately expressed through object-level exclusivity, but rather that the family plays a larger role in contributing to genre-level openness just as schooling plays a larger role in contributing to object-level exclusivity.4 Lizardo (2018) explores a crucial nuance regarding Bourdieu's argument, namely that the effects of family socialization and formal schooling are contingent.…”
mentioning
confidence: 99%
“…It is necessary to insert these values into learning on campus. It is because children will change the lifestyle of their parents, as well as on-campus (Nagel & Lemel, 2019). The consumption patterns in our lives do not only include eating and drinking, but they also include houses.…”
Section: Resultsmentioning
confidence: 99%
“…The condition of their house will affect the mindset of the students (Nagel & Lemel, 2019). Most of the students come from rural areas, and their house mostly comprises permanent walls of sand and cement.…”
Section: Resultsmentioning
confidence: 99%